Controlling mechanisms and cross linkages of ecosystem metabolism and atmospheric CO2 flux in the northern South China Sea. (March 2020) - Hung, J.-J.; Wang, Y.-J.; Tseng, C.-M.; Lee Chen, Y.-L.
Abstract: This study aims to understand the controlling mechanisms of ecosystem metabolic states and air-sea CO2 fluxes and their cross linkages in the northern South China Sea (NSCS). The integrated gross production (IGP), integrated dark community respiration (IDCR), and integrated bacterial respiration (IBR) were all higher in summer than in winter ranging from 851, 435, and 243 to 5032, 10707, and 7547 mg C m −2 d −1, respectively. The discrete estimates of gross production (GP) and dark community respiration (DCR) were modulated by temperature, salinity and nutrient availability through different mechanisms in summer and winter and in shallow (Zhujiang River plumes and shelves) and deep (slope and basin) sampling stations. GP was correlated with DCR ( r = 0.74, p < 0.0001), which in turn was largely attributed (65%) to bacterial respiration in the NSCS. Most spatial and summer-winter variability in the IGP/IDCR ratios was less than 1 (heterotrophic), except for in two ratios in winter in the Zhujiang River plume. However, these ratios were higher in winter than in summer because of the vertical pumping of nutrient in winter. Given the higher level of seawater p CO2 in summer than in winter, the NSCS appears to act as a balance to minor source of atmospheric CO2 in summer but a sink in winter. The air−sea fluxes of CO2 and ecosystem metabolic states share a close link in summer but separate in winter. Internal and external sources of dissolved organic carbon may play a key role in causing the heterotrophic conditions and atmospheric CO2 sink in winter. Highlights: Monsoon shifts and river inputs determine oceanic conditions in summer and winter. NSCS was heterotrophic in two seasons except for Zhujiang River plume in winter. NSCS was an atmospheric CO2 sink in winter but a source or in balance in summer. Variability of T, nutrients, DOC and POC determine metabolic states and CO2 fluxes. Metabolic states and CO2 fluxes link closely in summer but separate in winter.